West African provenance for Saxo-Thuringia (Bohemian Massif): Did Armorica ever leave pre-Pangean Gondwana? - U/Pb-SHRIMP zircon evidence and the Nd-isotopic record. - Linnemann, U; McNaughton, Neal; Romer, R; Gehmlich, M; Drost, K; Tonk, C (Springer Verlag, 2004)
Neoproterozoic rocks in the Saxo-Thuringian part of Armorica formed in an active margin setting and were overprinted during Cadomian orogenic processes at the northern margin of Gondwana. The Early Palaeozoic overstep sequence in Saxo-Thuringia was deposited in a Cambro-Ordovician rift setting that reflects the separation of Avalonia and other terranes from the Gondwana mainland. Upper Ordovician and Silurian to Early Carboniferous shelf sediments of Saxo-Thuringia were deposited at the southern passive margin of the Rheic Ocean. SHRIMP U/Pb geochronology on detrital and inherited zircon grains from pre-Variscan basement rocks of the northern part of the Bohemian Massif (Saxo-Thuringia, Germany) demonstrates a distinct West African provenance for sediments and magmatic rocks in this part of peri-Gondwana. Nd-isotope data of Late Neoproterozoic to Early Carboniferous sedimentary rocks show no change in sediment provenance from the Neoproterozoic to the Lower Carboniferous, which implies that Saxo-Thuringia did not leave its West African source before the Variscan Orogeny leading to the Lower Carboniferous configuration of Pangea. Hence, large parts of the pre-Variscan basement of Western and Central Europe often referred to as Armorica or Armorican Terrane Assemblage may have remained with Africa in pre-Pangean time, which makes Armorica a remnant of a Greater Africa in Gondwanan Europe. The separation of Armorica from the Gondwana mainland and a long drift during the Palaeozoic is not supported by the presented data.